Analisis Faktor Keberhasilan Inseminasi Buatan Pada Ternak Sapi Bali di Kecamatan Atambua Selatan Kabupaten Belu - Benedikta Salan; Agustinus A. Dethan; Theresia I. Purwantiningsih (JAS, 2021)
This research was conducted in South Atambua District, Belu Regency for 5 months. The purpose of this study was to determine the success factors of artificial insemination of bali cattle in Atambua Selatan District. In this study using a survey method, data collection was done by interview and observation. The population of acceptors in this study amounted to 50 farmers with 523 cattle. The variables observed in this study were the characteristics of the breeder, the pattern of livestock rearing, the number of livestock ownership, Service Per Conception (S/C), Conception Rate (CR), and Calving Interval (CI). The results showed that the success rate of Artificial Insemination in Atambua Selatan District was based on Service per Conception with an average S/C value of 1.77; The Conception Rate is 48.63% and the Calving interval is 413.20 months. Factors that influence the success rate of Artificial Insemination in Atambua Selatan District based on Service Per Conception, Conception Rate and Calving interval, namely semen quality, inseminator skills, estrus detection and reporting estrus, AI techniques, feed quality and quantity.